Within-system agreement between real-time and post-processed data using Dynamix from league optical tracking (Hawk-Eye) in professional football - Beato, M.; Troiani, P.; Zinco, C.; Pompa, D.; Bertollo, M.; Savoia, C. (Sports, 2026)
This study aimed to evaluate the within-system agreement and interchangeability of real-time and post-processed external load metrics in elite football. Data were collected from 50 official Serie A matches using Dynamix (K-Sport World S.R.L., Pesaro, Italy), the platform for acquiring and standardizing tracking inputs. SmartLive, a real-time monitoring module embedded within Dynamix, was compared with post-processed data from the league-approved optical tracking provider (Hawk-Eye Innovations Limited, Basingstoke, UK) in Serie A. The external load metrics analyzed included total distance covered; distances at speeds exceeding 15, 20, and 25 km·h-1; distances within the 15-20 km·h-1 and 20-25 km·h-1 ranges; distance covered during accelerations > 2 m·s-2 and decelerations < -2 m·s-2; and peak speed. Intraclass correlation coefficients (ICCs) demonstrated excellent agreement across all metrics, with values ranging from 0.929 to 0.999. Bland-Altman analysis revealed small mean differences between systems, indicating strong agreement. Overall, the findings confirm that both real-time and post-processed data are in close agreement across a wide range of performance metrics. Minor discrepancies were observed in intermediate speed zones and acceleration/deceleration events. This study provides the first validation of SmartLive`s within-system agreement with post-processed data, supporting its use alongside post-processed data in elite football environments.